Research on the Current Application Status of Digital Music Instruction in Primary and Secondary Education - Xiang, Xin (International Journal of Advanced AI Applications, 2025)
This study focuses on the current application status of digital music instruction in primary and secondary education. The research topic is grounded in the need for educational model innovation amidst the rapid advancement of technology. The research background highlights that digital teaching platforms have accelerated the integration of information technology into education, thereby enhancing learning efficiency. Through non-experimental empirical research employing descriptive statistical methods, a questionnaire survey was conducted among 126 music teachers from primary and secondary schools in City X. The findings reveal that while most teachers acknowledge the significance of digital resources in music instruction, there are limitations in their use of advanced functional software and tools. The study's conclusions emphasize that digital resources can broaden teaching experiences and stimulate students' creative thinking. It is crucial to strengthen teachers' digital literacy training to promote the in-depth development of music instruction practices in primary and secondary schools.